Model Komunikasi Dakwah Habib Ja'far dalam Youtube Chanel Noice “Berbeda Tapi Bersama Season 2” - Agung Muhammad Dzulkifli; Muhammad Zaky Safnazzahro (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Da'wah, as explained in the Qur'an, is an effort to invite individuals or groups, as well as the wider community, to embrace and apply Islamic teachings in daily life. This process is carried out in a sustainable and gradual manner, with the aim of internalizing, transmitting, and transforming the messages of Islamic teachings. This da'wah aims to direct humanity to goodness (al-khair), encourage good deeds (al-ma'ruf), and prevent bad actions (mungkar), so that they can achieve happiness in this world and the hereafter. The data used in this study were obtained through the author's observation of the YouTube account Noice (Different But Together). This article focuses on the implementation of da'wah activities on YouTube, as well as the oral and visual expressions used in these activities. The main methods applied by Habib Husein Jafar al-Hadar in his da'wah include emphasizing the themes of love, peace, and tolerance, using language that appeals to the younger generation, collaborating with popular YouTubers among young people, and delivering easy-to-understand da'wah material. Based on these findings, this article concludes that Habib Husein Jafar al-Hadar's da'wah activities have succeeded in attracting the attention of the current generation who often access YouTube, thus increasing the chances of da'wah collaboration to be well received.